The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/chd.12239
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Patient Simulation in a Pediatric Cardiology Rotation: A Unique Opportunity for Improving Resident Education

Abstract: Incorporation of HFPS into a preexisting pediatric cardiology rotation was feasible and well received. Our study suggests that simulation promotes increased confidence and may modestly improve clinical reasoning compared to traditional educational techniques. Targeted simulation sessions may readily be incorporated into pediatric subspecialty rotations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…However, as classroom and simulation training take time away from clinical responsibilities, these methods require evidence demonstrating effectiveness. Two recent small, single‐center studies incorporating simulation into pediatric cardiology resident education have demonstrated improvement in cardiology knowledge . Our study suggests that the primary educational interventions (bedside or simulation) should focus on helping learners build a framework for identifying and providing initial, emergent management to children who may require cardiology care.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, as classroom and simulation training take time away from clinical responsibilities, these methods require evidence demonstrating effectiveness. Two recent small, single‐center studies incorporating simulation into pediatric cardiology resident education have demonstrated improvement in cardiology knowledge . Our study suggests that the primary educational interventions (bedside or simulation) should focus on helping learners build a framework for identifying and providing initial, emergent management to children who may require cardiology care.…”
Section: Discussionmentioning
confidence: 80%
“…The previous studies pertaining to resident education in cardiology have considered the best methods for teaching specific, investigatordriven objectives including electrocardiogram (EKG) interpretation, auscultation, and management of simulated patients. [6][7][8][9][10] Although these studies have demonstrated positive outcomes, self-reported needs of learners were not emphasized. Self-assessment data suggest that pediatric residents can develop goals related to personal limitations, with this ability improving throughout training.…”
mentioning
confidence: 99%
“…These findings were in accord with educational research that has shown that medical simulation improves clinical competence in high acuity situations and teamwork behaviors. 2,4,17 Lessons Learned In reflecting on our experience, we noted several positive outcomes that were not directly evaluated in the pre-and postparticipation surveys. First, the critical action checklists used to guide the discovery phase of the debrief, were easily remembered and valued by participants.…”
Section: Discussionmentioning
confidence: 99%
“…13 A standardized program that incorporates simulationbased instruction may serve to improve delivery of patient care and enhance the quality of a residency or fellowship training program. [10][11][12][14][15][16] In an era of patient outcomes and quality improvement, the mantra of "see one, do one, teach one" may simply not suffice.…”
Section: Discussionmentioning
confidence: 99%